Investigating status demotion in hierarchical loyalty programs - Ramaseshan, Balasubramani; Ouschan, Robyn (Emerald Group Publishing, 2017)
© 2017, © Emerald Publishing Limited. Purpose: The purpose of this paper is to extend research on customer loyalty status and customer demotion by investigating if the effect of demotion on customer attitudinal and behavioral responses is the same for top-tier and low-tier customers in the context of airlines. Design/methodology/approach: A survey was conducted with travelers intercepted at large airport terminals in Australia. Multivariate analyses examined group differences across status change (no change vs demoted) and status level (high status vs low status). Multi-group moderation structural equation modeling (SEM) analysis tested the moderating role of status (high status vs low status) on the effects of demotion on the relationship between customers’ attitudes and loyalty intention, and between loyalty intention and share of wallet. Findings: This study shows that the detrimental effects of demotion on the relationship between customer satisfaction/commitment/perceived betrayal on loyalty intentions, and on the relationship between loyalty intentions and share of wallet are stronger for “high status” than “low status” customers. Research limitations/implications: A cross-sectional design was employed to investigate customer demotion in the airline industry. Future studies could investigate different types of demotions in other industries by employing a longitudinal design. Practical implications: The study provides new insight about the effects of status demotion and highlights that service firms could be jeopardizing the loyalty of numerous valuable customers, especially among the “high status” customer group. Originality/value: This study reveals loyalty status moderates the effect of demotion on customer attitudinal responses and loyalty behaviors. It draws on social identity, social comparison, emotion and equity theories to explain the different effects of demotion on customers from different status level groups.